Palladium‐Catalyzed Carbonylations of Arylboronic Acids: Synthesis of Arylcarboxylic Acid Ethyl Esters. Issue 14 (12th October 2015) - Liang, Apeng; Han, Shuaijun; Wang, Liang; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract: An approach for the palladium‐catalyzed ethoxycarbonylations of arylboronic acids using diethyl pyrocarbonate as carbon monoxide/carbon dioxide (CO/CO2 ) surrogate in moderate to good yields has been investigated. Abstract :